2016
DOI: 10.3389/fnbeh.2016.00075
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Mating-Induced Fos and D2-Like Dopamine Receptors in the Medial Preoptic Area: Influence of Sexual Experience

Abstract: Dopamine in the medial preoptic area (mPOA) stimulates sexual activity in males. This is evidenced by microdialysis and microinjection experiments revealing that dopamine receptor antagonists in the mPOA inhibit sexual activity, whereas agonists facilitate behavior. Microdialysis experiments similarly show a facilitative role for dopamine, as levels of dopamine in the mPOA increase with mating. While the majority of evidence suggests an important role for dopamine receptors in the mPOA in the regulation of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Across development, CRFR1-GFP-ir within the MPOA was stable between P0 and P21. The MPOA is known to have anatomical sex differences (Morris et al, 2004), and influence sexual behavior in rodents (Nutsch et al, 2016). Although, no obvious sex differences in receptor protein were apparent, previous work in rats has demonstrated a sex difference in MPOA CRF, with females exhibiting a higher density (McDonald et al, 1994;Funabashi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Across development, CRFR1-GFP-ir within the MPOA was stable between P0 and P21. The MPOA is known to have anatomical sex differences (Morris et al, 2004), and influence sexual behavior in rodents (Nutsch et al, 2016). Although, no obvious sex differences in receptor protein were apparent, previous work in rats has demonstrated a sex difference in MPOA CRF, with females exhibiting a higher density (McDonald et al, 1994;Funabashi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…MPOA neurons also mediate experience-dependent sexual arousal. Sexual experience facilitates all components of mating behaviors, and this facilitation is thought to be mediated by experience-induced changes in MPOA neurons, such as synaptic plasticity ( Jean et al, 2017 ), dopamine sensitivity ( McHenry et al, 2012 ; Nutsch et al, 2016 ), oxytocin sensitivity ( Gil et al, 2013 ), and neuropeptide precursor expression ( Maejima et al, 2018 ).…”
Section: Male Sexual Behaviormentioning
confidence: 99%
“…MPOA is one of the brain structures in which acquisition of sexual experience leads to an increase in Fos expression, and higher levels of neurotransmitters, receptors, or enzymes and hormones important for regulation of sexual activity (Hull and Rodríguez-Manzo, 2017). Specifically, it was shown that acquisition of sexual experience is associated with an increase in nitric oxide with higher levels of nitric oxide synthase (Dominguez et al, 2006), glutamate and dopamine (Will et al, 2014), D1 receptor signaling (McHenry et al, 2012) and D2 receptor signaling (Nutsch et al, 2016), and oxytocin receptors (Gil et al, 2013), and an increased number of neurons containing androgen receptors (Swaney et al, 2012). Moreover, acquisition of sexual experience and improvement in copulatory efficiency was shown to involve neuronal plasticity as measured by c-fos expression in the parieto-occipital cortex (Bialy et al, 1992;Bialy and Kaczmarek, 1996).…”
Section: Copulatory Efficiency (Copulatory Rate Factor)mentioning
confidence: 99%